STRATEGI PELAKSANAAN PILKADES BERBASIS E-VOTTING DI KABUPATEN SLEMAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Udaya Madjid; Layla Kurniawati; Indri Susiamti (Jurnal Academia Praja, 2025)
The electronic selection of village heads has been widely implemented in recent years. Sleman Regency is one of the regencies that conducts village head election using the e-votting method. Concerns about technological manipulation that could affect the vote counts for each candidate pair have been raised by a community group known as the “Manikmoyo” village head association. Puprose of this research is to understand the implementation of e-votting based village head elections in Sleman Regency, to identify the factors causing opposition, and to observe and formulated strategiest to be implemented by the Departement of Community and Village Empowerment of Sleman Regency. Data collection methods for this research include nterviews, observations, and gathering documents related to the implementation of e-votting based village head elections in Sleman Regency. The results of this research indicate that the role of the Department of Community and Village Empowerment as a leading sector in the e-votting based village head elections in Sleman Regency has been quite effective. The causes of opposition include public concerns about the adoption of the new technology as a votting method and issues related to data security and privacy. These concerns dominate the resistance to this technology in village head elections, as they relate to vote counts that will affect each candidate pair. The influencing factors consist of internal and external factors, followed by the determination of strategies for success based on SWOT analysis and litmust tests. The strategic issues identified include optimizing the high technology acceptance rate in Sleman Regency to conduct program socialization and various governmental activities related to technology implementation.